Healthy Lifestyle Education Through Play-Based Learning among Children Aged Three to Four Years: A Case Study in Indonesia - Prima Trisna Aji; Elinda Rizkasari; Arief Shofyan Baidhowy (Lia Center of Research and Education, 2026)
This study explores the implementation of healthy lifestyle education through play-based learning in early childhood education settings. Early childhood is a critical developmental stage during which children begin to form daily habits related to nutrition, hygiene, physical activity, rest, and emotional well-being. This qualitative case study was conducted in a pseudonymized early childhood education center in Indonesia and focused specifically on children aged 3–4 years (n = 15) over a two-week observation period. Data were collected through classroom observations, semi-structured interviews with the classroom teacher, and documentation of learning activities. The findings revealed that integrating health-related content into play-based activities encouraged active participation and meaningful learning. Twelve out of fifteen children consistently demonstrated improved hand-washing routines, greater willingness to engage in physical movement activities, and increased awareness of healthy food choices during the observation period. These changes were identified through systematic observation and teacher reflection rather than formal behavioral scoring. Parental involvement played an important role in reinforcing health-related routines at home, contributing to behavioral consistency across settings. Teachers reported that play-based learning made health education more natural, developmentally appropriate, and enjoyable for children. In this study, internalization is understood as children’s consistent and self-initiated enactment of healthy behaviors within play and daily routines, supported by social interaction and repetition, rather than explicit verbal understanding of underlying health concepts. This study contributes to the literature by demonstrating how healthy lifestyle behaviors can be naturally embedded in early learning routines for children aged 3–4 years without direct instruction, expanding understanding of play-based learning as a mediating pathway for early health-habit internalization within Asian early childhood education contexts.